Heteroatomic Conjugated Polymers and the Spectral Tuning of Electroluminescence via a Supramolecular Coordination Strategy. Issue 22 (26th September 2016) - Lin, Jinyi; Liu, Bin; Yu, Mengna; Xie, Linghai; Zhu, Wensai; Ling, Haifeng; Zhang, Xinwen; Ding, Xuehua; Wang, Xuhua; Stavrinou, Paul N.; Wang, Jianpu; Bradley, Donal D. C.; et al.
Abstract : The unique electronic structures of heteroatomic conjugated polymers (HCPs) offer an attractive platform to tune optoelectronic properties via a supramolecular coordination strategy. This study reports on an sp 2 nitrogen heteroatom containing fluorene‐based copolymer namely poly(9, 9‐dioctylfluorene‐ co‐ 9, 9‐dioctyldiazafluoren‐2, 7‐yl) (PF8‐ co ‐DAF8), with ≈20% DAF8 units. Tuning the optoelectronic properties of PF8‐ co ‐DAF8 via supramolecular coordination with a Lewis acid (B(C6 F5 )3 or AlCl3 ) is explored. Formation of either the PF8‐ co ‐DAF8‐B(C6 F5 )3 or PF8‐ co ‐DAF8‐AlCl3 adducts reduces the optical gap and causes an attendant redshift of the photoluminescence spectra. Controlling the degree and strength of the coordination allows the emission color to be tuned from blue through to green and yellow. This strategy is successfully implemented for polymer light‐emitting diodes, confirming the large degree of spectral tuning whilst maintaining good device performance. Maximum luminous efficiencies, η ≈ 1.55 cd A −1 @ 2120 cd m −2, 1.32 cd A −1 @ 1424 cd m −2, and 2.56 cd A −1 @ 910 cd m −2 are, respectively, recorded for the blue‐emitting diodes with Commission Internationale de L'Eclairage (CIE) (x, y) coordinates = (0.16, 0.16), the white‐emitting diodes with CIE (x, y) = (0.28, 0.38) and the green‐emitting diodes with CIE (x, y) = (0.33, 0.52). The results highlight the versatility of the supramolecular coordination strategy in modifying the electronic structure of HCPs. Abstract : Supramolecular coordination is a powerful tool to tune optoelectronic properties in heteroatomic conjugated polymers. Varied fractions of sp 2 nitrogen‐containing diazafluorene units are introduced into fluorene‐based copolymers and via controlled coordination with Lewis acids provide a single material system capable of extended spectral performance. Polymer light‐emitting diodes based there on demonstrate high efficiency and broadly tuneable (blue, white, and green) operation.